MODERN REQUIREMENTS FOR TEACHERS OF THE PREPARATORY GROUP OF PRESCHOOL EDUCATIONAL ORGANIZATIONS - Adjumerova Arzu Asanovna (Modern American Journals, 2025)
This article analyzes from a scientific point of view the modern requirements for educators of the preparatory group of preschool educational organizations. Preschool education is an important stage in the development and education of children. Educators play an important role in the development of children's personality, social skills and the educational process. Educational knowledge, professional qualifications, social and emotional skills, as well as the ability to use innovative technologies are important for modern educators. This article presents comprehensive ideas about the importance of each requirement, their impact on the activities of educators and how they can help improve the educational process.
Keywords: Preschool education, educators, educational requirements, professional qualifications, social skills, emotional skills